Analisis Wacana Kritis Model Teun Van Dijk pada Pemberitaan Kasus Perisakan Santri di Kediri dalam Berita Daring - Syaifullah; Herdi; Abbas, M. Fadhly Farhy (Indra institute Research & Publication, 2024)
This research aims to analyze text structure, social cognition, and social context on the online news portals Tempo.co, Detik.news, and Kompas.tv regarding cases of bullying against Islamic boarding school students in Kediri. The data source for this research comes from an online news page about cases of bullying against Islamic boarding school students in Kediri. This research uses a qualitative approach using content analysis methods. The data collection technique used is documentation, listening and taking notes. Data analysis techniques include data editing, data presentation, and drawing conclusions. The results of this research show that the three online news portals have the same theme and topic, namely informing about cases of student bullying committed by fellow students in Kediri. These three news items have fulfilled Teun A. Van Dijk's discourse analysis model, namely (1) macro structure; (2) superstructure, and (3) microstructure. Based on critical discourse analysis of news on the online news portals Tempo.co, Detik.news, and Kompas.tv, it can be concluded that the three news items meet the level of critical analysis of Teun A. Van Dijk's model (1) text structure; (2) social cognition; and (3) social context.